Stress relief investigation using creep model considering back stress in welded rotor. (June 2020) - Hu, Mengjia; Li, Kejian; Li, Shanlin; Cai, Zhipeng; Pan, Jiluan
Abstract: Welded ferritic steel rotors are a critical dynamic component of fossil-fired power plants. It is essential to investigate residual stress distribution in welded rotors and investigate methods to reduce residual stress for improving structural integrity. In the present study, a creep model that considers back stress is introduced in the residual stress relief simulation of welded ferritic steel rotors in furnace-based uniform post weld heat treatment. Comparisons between the new and Norton–Bailey creep model were conducted numerically, and results indicate that the new creep model can inherit the as-welded residual stress distribution and simulate post weld heat treatment (PWHT) residual stress more accurately, which has been validated with experimental results. Furthermore, it is discovered that the dominant stress relief mechanism of ferritic steel is creep-strain-induced stress relaxation. The creep strain occurred primarily in a short time with a dislocation creep mechanism, and the holding time hardly affected the generation of creep strain. Increasing the PWHT temperature enables more stress relaxation at low temperatures. Additionally, stress relaxation almost no longer occurred when the PWHT temperature exceeded a critical value (approximately 520 °C in this study) that was lower than the recrystallisation temperature. Hence, it is important to control the welded residual stress. Highlights: Creep model considering back stress has been introduced in residual stress relief simulation of welded ferritic steel rotor. PWHT stress distribution has a certain inheritance to as welded residual stress, explained with new creep model. PWHT has limitation on eliminating as welded stress, and it is necessary to control as welded residual stress.